2015
DOI: 10.1093/jac/dkv053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for carriage of antimicrobial-resistant Escherichia coli on household and small-scale chicken farms in the Mekong Delta of Vietnam

Abstract: Escherichia coli multidrug resistant to widely available antibacterials poses a threat to humans, their poultry and their environment when the prevalence is high, and containment is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 37 publications
4
75
3
Order By: Relevance
“…All studies report types and classes of antimicrobials used on farms over a specified period of time. In three publications (two of which relate to the same study farms), quantitative data are also presented [16,18,23]. In two of these studies [16,18] consumption is presented in terms of grams of antimicrobial compound to produce one kilogram of chicken or pig produced, whereas in the other [23], consumption for chickens was expressed as “treatment incidence” [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies report types and classes of antimicrobials used on farms over a specified period of time. In three publications (two of which relate to the same study farms), quantitative data are also presented [16,18,23]. In two of these studies [16,18] consumption is presented in terms of grams of antimicrobial compound to produce one kilogram of chicken or pig produced, whereas in the other [23], consumption for chickens was expressed as “treatment incidence” [24].…”
Section: Resultsmentioning
confidence: 99%
“…In three publications, AMR was investigated in both E. coli and NTS isolates. The majority of publications included data from Thailand (20) [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] and Vietnam (15) [18,23,45,46,47,48,49,50,51,52,53,54,55]. One publication was found with data from each of Cambodia, Indonesia, Lao PDR and Malaysia [56,57,58,59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be also possible that antimicrobial resistant E. coli might be transmitted from food-animals and raw foods to human. The previous studies from southern Vietnam suggested that food-animals and raw foods could be a potential reservoir of antimicrobial resistance bacteria that disseminated to human [31, 49]. It was found that commensal E. coli isolates on household and small-scale chicken farms in the Mekong Delta of Vietnam have high prevalence of resistance to TET, AMP, SXT, and CHL ( >60%) and MDR (81.3%), indicating the high risk of transmission of antimicrobial-resistant E. coli to community [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much attention has been paid to ESBL-producing E. coli in healthy individuals as well [1, 4, 5, 15, 21, 22, 32, 42, 44, 47, 50]. In Vietnam, prevalence of antimicrobial resistance in commensal E. coli was investigated in only children [14], raw food samples [49], household and small chicken farms [31]. However, comprehensive studies regarding analysis of antimicrobial resistance, ESBL type and virulence gene profile of commensal E. coli in adults were not conducted.…”
mentioning
confidence: 99%